Study on the effect of sucrose as the alternative admixture in ordinary portland cement (OPC) binder (OPC) binder - Siti Nur Robiatun Adayiah , Shaikh Abdullah (2014)
This research aims to investigate the effect of sucrose as the alternative admixture in Ordinary Portland Cement (OPC) binder. Chemical admixtures like sucrose are the ingredients that will be used in concrete other than Portland cement, water, and aggregate that is added to the mix directly before or during mixing. The admixtures primarily used to cut the cost of concrete construction, modify the properties of hardened concrete and also ensure the quality of concrete during mixing, transporting, placing, and curing. Furthermore, Ordinary Portland Cement binder by cube 50mm x 50mm x 50mm in size will be prepared. An about 65 samples will be tested during the study where the test that carried out to measure the workability test, compressive strength test and porosity test at 1 day, 7 days and 28 days. In addition, the effects of sucrose at concentrations of 0.50, 0.75, 1.00, 1.25 and 1.50 milimole/liter will be used as the alternative admixture in Portland cement paste. Based on Vicat setting time result, sucrose tends to increase the setting time of Portland cement paste. Furthermore, sucrose causes higher retardation when added a few minutes after the mixing of water and cement. Compressive strength of sucrose shows that as the curing time increase, the compressive strength of paste develops. Based on t - test analysis, 1.25 milimole/l of sucrose are the optimum percentages of admixtures that show higher compressive strength when compared to the control specimen. However, by the inclusion of sucrose was provided a unique correlation between porosity and compressive strength. It is because in sucrose-added system, the increasing compressive strength is followed by the increasing porosity of Ordinary Portland cement paste. Keywords Ordinary Portland cement paste, sucrose, workability, compressive strength, porosity